Endocarp Morphology of Premna (Lamiaceae) in Thailand and Its Taxonomic Significance - Jiratthi Satthaphorn; Alan J. Paton; Pornsawan Sutthinon; Charan Leeratiwong (Plants)
Fruits and endocarps of 21 species within the genus Premna (Lamiaceae) in Thailand were examined using light (LM) and scanning electron microscopy (SEM) to evaluate taxonomic relevance. Overall, mature fruits were classified into two types: fully developed mericarp (fruit type I) and partly developed mericarp (fruit type II), with three shape patterns: broadly obovoid, narrowly obovoid, and clavoid. Fruit size ranged from 1.52 to 7.48 mm in length and 0.98 to 7.71 mm in width. In LM investigations, the endocarps were classified into three types based on the presence and shape of the protruding structure: saccate-like (protrusion type I), thorn-like (protrusion type II), and no protrusion (protrusion type III). The examination of endocarps under SEM showed that they consist of multilayers of sclerenchyma cells. The shape of the sculpturing cells on the endocarp surface can be divided into two patterns: irregular tetragonal and polygonal, with distinct or obscure straight cell faces. The morphological comparison and phenetic analyses using factor analysis of mixed data (FAMD) show that fruit and endocarp characteristics of Premna hold significant taxonomic value for distinguishing certain related species and classifying within the genus in Thailand. From the first two FAMD dimensions, fruit shape, shape of sculptured cells on the endocarp, and protrusion type of the endocarp are considered as the most significant contributing variables. The findings also support the reinstatement of species previously synonymized with P. serratifolia, namely P. cordifolia, P. paniculata, and P. punctulata.